Green Investment Regime: Judul: Analysis of the Implementation of Green Economy-Based Maritime Tourism Village Potential Development - Muh. Zainuddin Badollahi; Siti Hajar N. Aepu; Risma Ariyani (Newinera Publisher, 2022)
In this study, we delve into the concept of the